Bioinspired total synthesis of tetrahydrofuran lignans by tandem nucleophilic addition/redox isomerization/oxidative coupling and cycloetherification reactions as key steps. Issue 5 (8th January 2018) - Jagtap, Pratap R.; Císařová, Ivana; Jahn, Ullrich
Abstract : Three steps suffice to complete a bioinspired total synthesis of tetrahydrofuran lignans using tandem addition/isomerization/dimerization and cycloetherification reactions. Abstract : A very short three-step approach to trans, trans, trans -2, 5-diaryl-3, 4-dimethyltetrahydrofuran lignans is reported. The carbon skeleton is assembled in a single step based on an unprecedented tandem reaction consisting of 1, 2-addition of aryllithium reagents to α, β-unsaturated aldehydes, ruthenium-catalyzed redox isomerization of the resulting alkoxides to enolates and their dimerization triggered by single electron oxidation. The resulting 2, 3-dialkyl-1, 4-diketones form with moderate to good d / l -diastereoselectivity and are transformed to the target tetrahydrofuran lignans by reduction and diastereoselective cycloetherification.